Entries computerized and industry Historical Dictionary - Alani, Luma F. (Al-Adab Journal, 2019)
With the development of modern technologies, and enter all fields of science and knowledge it was necessary to enter in linguistics field, and so I wanted to clear the Iraqi world's linguistic project Prof. Dr. Ali Al-Qasimi in the Historical Dictionary of industry, and apply it on the Arabic language is a huge and complex project in which he tried to cover all the doors of the Arabic language to establish an integrated encyclopedia, and despite the foot and received from the support and admiration, but such projects is difficult to apply smoothly. I hope that a precedent Qasimi project to confirm that the Arabic language is going to keep up with the technical evolution of sync with scientific progress in all its aspects